THE EFFECT OF PROFITABILITY, SOLVENCY AND LIQUIDITY ON COMPANY VALUE WITH DIVIDEND POLICY AS INTERVENING VARIABLES - Aditya Agung SetiaBudi; Sulastri Sulastri; Yuliani Yuliani (SEAN Institute, 2023)
Study This aim For know “ Influence Profitability, Solvency, and Liquidity to Company Value with Policy Dividend as intervening variable ”. Sample study This taken from company manufacturers listed on the Indonesia Stock Exchange (IDX) in 2018-2022 with purposive sampling method. Obtained 29 Companies as sample, which is observed for 5 years with total observations as many as 145. Data collection techniques using documentation from report finance published on the IDX's official website, namely www.idx.co.id. Analysis used_is use analysis path. Research results This show that Profitability influential positive and significant to Policy Dividend, Solvability No influential to Policy Dividend, Liquidity influential in a manner positive and significant to Policy dividend. Profitability influential positive and significant on Firm Value, Solvability No influential on Company Value, Liquidity influential significant on Corporate Values, Policies Dividend influential positive and significant to Company Value.